2011
DOI: 10.4278/ajhp.090325-arb-115
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Walking Program for Mexican-American Women Living in Colonias at the Border

Abstract: Culturally sensitive programs promoting walking in underserved, minority populations are promising in reducing physical activity disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…On the other hand, only five studies focused on the promotion of PA as their primary outcome (Staten et al, 2004;Gomes and Duarte, 2008;Ayala, 2011;Mier et al, 2011;Coleman et al, 2012). Analysis of the samples revealed that, in terms of ethnicity/race, half of the interventions were applied in Hispanic populations (or descendants) (Staten et al, 2004;Balcázar et al, 2005;Staten et al, 2005;Larkey, 2006;Babamoto et al, 2009;Castillo et al, 2010;Ayala, 2011;Mier et al, 2011;Ruggiero et al, 2011;Spencer et al, 2011;Coleman et al, 2012;Duggan et al, 2014), and five (19.2%) in Blacks (Becker et al, 2005;Plescia et al, 2008;Treadwell et al, 2010;Spencer et al, 2011;Cene et al, 2013).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…On the other hand, only five studies focused on the promotion of PA as their primary outcome (Staten et al, 2004;Gomes and Duarte, 2008;Ayala, 2011;Mier et al, 2011;Coleman et al, 2012). Analysis of the samples revealed that, in terms of ethnicity/race, half of the interventions were applied in Hispanic populations (or descendants) (Staten et al, 2004;Balcázar et al, 2005;Staten et al, 2005;Larkey, 2006;Babamoto et al, 2009;Castillo et al, 2010;Ayala, 2011;Mier et al, 2011;Ruggiero et al, 2011;Spencer et al, 2011;Coleman et al, 2012;Duggan et al, 2014), and five (19.2%) in Blacks (Becker et al, 2005;Plescia et al, 2008;Treadwell et al, 2010;Spencer et al, 2011;Cene et al, 2013).…”
Section: Resultsmentioning
confidence: 94%
“…Analysis of the samples revealed that, in terms of ethnicity/race, half of the interventions were applied in Hispanic populations (or descendants) (Staten et al, 2004;Balcázar et al, 2005;Staten et al, 2005;Larkey, 2006;Babamoto et al, 2009;Castillo et al, 2010;Ayala, 2011;Mier et al, 2011;Ruggiero et al, 2011;Spencer et al, 2011;Coleman et al, 2012;Duggan et al, 2014), and five (19.2%) in Blacks (Becker et al, 2005;Plescia et al, 2008;Treadwell et al, 2010;Spencer et al, 2011;Cene et al, 2013). In relation to clinical conditions, nine studies involved samples at risk of or with diabetes mellitus type II (Babamoto et al, 2009;Castillo et al, 2010;Comellas et al, 2010;Treadwell et al, 2010;Allen et al, 2011;Spencer et al, 2011;Islam et al, 2013a;Islam et al, 2013b;Duggan et al, 2014) and four studies included overweight/obese individuals (Folta et al, 2009;Treadwell et al, 2010;Mier et al, 2011;Jennings et al, 2013) (Table 1).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations